2009
DOI: 10.1093/ndt/gfp439
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of asymmetrical dimethyl-L-arginine accumulation and endothelial progenitor cell deficiency on renal function decline during a 2-year follow-up in stable angina

Abstract: Elevated ADMA and EPC deficiency may synergistically contribute to accelerated renal function decline in stable angina. This could result from the impairment of the EPC-dependent endothelial renewal in the kidney, an NO-dependent process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 55 publications
0
13
0
1
Order By: Relevance
“…In this study, elevated plasma ADMA levels were also observed in patients with macroalbuminuria. Finally, ADMA has been shown to inhibit mobilization, differentiation, and function of endothelial progenitor cells (32), and recently, both ADMA accumulation and epithelial progenitor cell deficiency have been found to synergistically accelerate the deterioration of renal function in patients with stable angina (33). In summary, it may be hypothesized that in patients with mild to moderate CKD, the association between ADMA and long-term adverse events may be attributed to the reducing NO bioavailability/impaired endothelial dysfunction and/or increased oxidative stress and/or suppressed function of endothelial progenitor cells via inhibition of NO synthase and its association with proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, elevated plasma ADMA levels were also observed in patients with macroalbuminuria. Finally, ADMA has been shown to inhibit mobilization, differentiation, and function of endothelial progenitor cells (32), and recently, both ADMA accumulation and epithelial progenitor cell deficiency have been found to synergistically accelerate the deterioration of renal function in patients with stable angina (33). In summary, it may be hypothesized that in patients with mild to moderate CKD, the association between ADMA and long-term adverse events may be attributed to the reducing NO bioavailability/impaired endothelial dysfunction and/or increased oxidative stress and/or suppressed function of endothelial progenitor cells via inhibition of NO synthase and its association with proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…We studied the previously characterized group of 80 non-diabetic men with stable angina who underwent successful elective complex coronary angioplasty with implantation of ≥1 bare-metal stent in our tertiary care center due to the presence of a diameter stenosis of ≥70% of ≥1 major epicardial artery segment [24,25]. Prior to the hospitalization, the patients were on low-dose aspirin, angiotensin-converting enzyme inhibitors (ACEI) and statins for ≥3 months and this medication was maintained after discharge and supplemented by clopidogrel following current practice guidelines (Tables 1 and 2).…”
Section: Methodsmentioning
confidence: 99%
“…The study subjects were being treated with low-dose aspirin, statins and angiotensinconverting enzyme inhibitors (ACEI) for ≥3 months prior to admission to limit the heterogeneity of the patients in terms of the use of drugs known to improve CV outcome in CAD, as described previously (Surdacki et al 2010). The study population was divided into 2 groups according to metformin use for at least 1 year before index hospitalization.…”
Section: Patientsmentioning
confidence: 99%
“…Exclusion criteria included overt heart failure, congenital heart disease, significant valvular heart disease, arterial hypertension uncontrolled adequately by drugs, major surgery during past 6 months, any infections within preceding 2 months, estimated glomerular filtration rate (eGFR) below 45 mL/min per 1.73 m 2 of body surface area according to the Chronic Kidney Disease Epidemiology Collaboration formula, endocrine disorders other than diabetes, abnormal liver function, coexistent inflammatory or malignant diseases, relevant laboratory abnormalities in the routine blood and urine analysis, and any chronic non-CV or non-diabetic medication (Surdacki et al 2010).…”
Section: Patientsmentioning
confidence: 99%